2015
DOI: 10.1111/hiv.12262
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection is associated with an increased prevalence of coronary noncalcified plaque among participants with a coronary artery calcium score of zero: Multicenter AIDS Cohort Study (MACS)

Abstract: Objectives HIV infected individuals bear increased cardiovascular risk even in the absence of traditional cardiovascular risk factors. In the general population, coronary artery calcium (CAC) scanning is of value for cardiovascular risk stratification, but whether a CAC score of zero implies a low non-calcified coronary plaque burden in HIV infected persons is unknown. Methods We assessed the prevalence of non-calcified coronary plaque and compared non-calcified coronary plaque burden between HIV infected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…By 2016, the numbers of health care visits by HIV status were similar. In analyses restricted to HIV-positive participants, we found that having a detectable viral load, CD4 less than 500, and ART adherence were not associated with a greater likelihood of polypharmacy, while ART use was associated with polypharmacy; this finding could be related to increased dyslipidemia and cardiovascular disease reported in association with ART use among HIV-positive persons [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…By 2016, the numbers of health care visits by HIV status were similar. In analyses restricted to HIV-positive participants, we found that having a detectable viral load, CD4 less than 500, and ART adherence were not associated with a greater likelihood of polypharmacy, while ART use was associated with polypharmacy; this finding could be related to increased dyslipidemia and cardiovascular disease reported in association with ART use among HIV-positive persons [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from MACS revealed HIV-infected men were more likely to have non-calcified plaque than HIV-uninfected men. 18, 40 . However, we did not find any association of frailty with NCPS regardless of HIV-serostatus.…”
Section: Discussionmentioning
confidence: 99%
“…The CAC score though may underestimate atherosclerotic burden in patients with HIV, especially compared to other imaging modalities. Among patients with undetectable CAC, more patients with HIV have increased CIMT [24] and non-calcified plaque on cardiac computed tomography angiography (CCTA) [25] compared to patients without HIV. In addition to non-calcified plaque, CCTA can also detect high-risk morphologic features of coronary atherosclerosis such as plaque volume, low attenuation, positive remodeling, spotty calcification, and the napkin ring sign, which in the general population have been associated with culprit lesions in acute coronary syndrome [26].…”
Section: Insights From Cardiac Imaging Into the Unique Pathophysiologmentioning
confidence: 99%